Preparation of graft copolymers from Vietnam deproteinized natural rubber with acrylonitrile using tetraethylenepentamine and tert-butyl hydroperoxide radical initiators - Nguyen Thi Ngoc, Anh; Phan Minh, Quyet; Vu Trung, Nam; Nguyen Quynh, Vi; Than Van, Hau; Tran Quang, Tung; Nguyen Thu, Ha; Nguyen Ngoc, Mai; Tran Thi, Thuy (Vietnam Journal of Science and Technology, 2025)
Natural rubber is an unsaturated natural elastomer with many superior properties such as high strength, outstanding resilience, and high elongation at break. However, it lacks in some properties due to the unsaturation of carbon-carbon double bonds in the natural rubber backbone causes easy degradation and poor thermal stability.  Many techniques have been made use of improving its thermo-mechanical properties. In this study, the graft copolymerization of acrylonitrile onto deproteinization natural rubber was investigated to increase the thermal and mechanical properties of natural rubber. This process was performed successfully in latex using tetraethylenepentamine and tert-butyl hydroperoxide as radical initiators at 30 °C. The effects of acrylonitrile concentration on the conversion and grafting efficiency of the graft copolymerization were studied. The structural characterization of the obtain graft copolymer was carried out by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy. The improvement in thermal properties of the obtained products was confirmed by Thermal Gravimetric Analysis/Differential Thermal Gravimetric Analysis, which showed that at the optimal condition for graft copolymerization was at acrylonitrile of 15 wt.% per kg of rubber, where the maximum degradation occurred at 377 °C. The mechanical properties of the products were also studied via tensile testing, where the tensile strength of the graft copolymerization using at AN of 15 wt.% per kg of rubber (1.5±0.5MPa), nearly tripled when compared to virgin deproteinized NR (3.8±0.9MPa).